IMPLEMENTASI KOMPETENSI PEDAGOGIK GURU PENDIDIKAN AGAMA KATOLIK DALAM PEMBELAJARAN KONTEKSTUAL - Yulia Fitri; Lorensius Lorensius; Nikolaus Anggal (Lembaga Penelitian STKIP Widya Yuwana, 2026)
This study investigates the implementation of pedagogical competence among Catholic Religious Education (CRE) teachers at SD Negeri 004 Tering, East Kalimantan. Pedagogical competence serves as a foundation for effective instruction, particularly when integrated with the Contextual Teaching and Learning (CTL) approach that connects faith-based content to students’ real-life experiences. Using a descriptive qualitative design, data were collected through classroom observations, in-depth interviews, and document analysis involving one CRE teacher and nine students. The findings indicate that the teacher demonstrates comprehensive pedagogical competence across lesson planning, instructional delivery, and authentic evaluation aligned with the CTL framework. The integrated learning cycle consisting of planning, implementation, and reflection, illustrates how faith values are contextualized through discovery, questioning, and reflective activities. This process cultivates moral awareness, critical thinking, and spiritual sensitivity among students. The study concludes that the pedagogical competence of CRE teachers functions as a transformative medium linking faith teachings with everyday life, embodying the essence of learning by believing within the spirit of the Merdeka Curriculum.